Evaluación del impacto ambiental de los residuos sólidos generados en el mercado centro agrícola cantonal de pastaza, aplicando las normas mexicanas nmx-aa-0.15-0.19-0.22, para proponer un plan de manejo ambiental - Miranda Montahuano, Miguel Ángel (2016)
The work of investigation was developed in Puyo, in the market called Centro Agricola Cantonal de Pastaza; which is located in the north with Ceslao Marin street, in Alberto Sambrano’s street. Its main purpose was to contribute and to improve the different activities and services that this supply center brings to Puyo's poblation, through an environmental management plan that applies all the current Mexican rules. The description of the direct area and the involved actors in the same was developed, it was found 191 people from different genders and ages that work in Centro Agricola Cantonal de Pastaza. They were surveyed and trained, so according to their knowledge, start the environmental management plan following its purpose, which is: to control, mitigate and minimise the environmetal impact that is generated because of the solid waste. In many occassions it is produced by the poblation that increases every day. Through the work developed in the market, the characterization of the solid waste produced during the week were known with the quantity of generation of 1.726,2 Kg/week, with an averge Per Capita of 1,29 Kg/habitant/day, worked with the quartet C and D giving the quantity of 461,6 Kg/week, giving an average of volumetric weight of 333,29 kg/m³. Revealing that the 82% of waste is Organic and the 18% is inorganic. The environment management plan for the Pastaza’s market, manifest the following programs, the control of the solid waste, the classification and waste management through colourful bins, training and ambiental education, these programs are framed in the prevention, control and mitigation of environmental impacts.